Earthquake Preparedness Among Nursing Students - Rahayu Rahayu; Azizah Khoiriyati (Universitas Muhammadiyah Yogyakarta, 2019)
Background: Nursing science students are prospective nurses who have an important role in disaster management, including disaster mitigation, disaster response, and post-disaster rehabilitation. Objective: This study aimed to investigate the earthquake disaster preparedness in nursing science students of Universitas Muhammadiyah Yogyakarta. Method: This study was a non-experimental study utilizing the quantitative method and descriptive survey design. The population of this study was active students of Nursing Study Program at Universitas Muhammadiyah Yogyakarta with a sample of 217 respondents. The sample was obtained using a proportional convenience sampling technique. The data were obtained through an instrument in the form of a valid and reliable earthquake preparedness questionnaire. The obtained data were then analyzed by using descriptive statistical analysis. Results: The findings of this study indicated that the level of students' earthquake preparedness was still in the low category. The findings on the parameters supported it. Students' knowledge and attitude towards an earthquake risk were in the high category while the emergency response plan parameter was included in the low category. The disaster warning system parameter was in the good category. At last, the resource mobilization parameter obtained was in a low category. Conclusion: Thus, it was concluded that the level of earthquake preparedness of Nursing Science students of Universitas Muhammadiyah Yogyakarta was in a low category. These findings explained the urge for disaster preparedness for students in the Nursing Science Study Program. Accordingly, routine training in earthquake disaster management is needed to improve students' disaster preparedness.